Religious Moderation in Islamic Groups in the History of the Basic Consesus of the Indonesian State - Hariyanto, Didik; Islamy, Athoillah (Al-Adalah: Jurnal Hukum dan Politik Islam, 2023)
This research intends to identify the manifestations of religious moderation by Islamic groups in the history of the consesus of the basic formulation of the Indonesian state. This qualitative research uses a normative-historical approach. Various scientific literature on ideological struggles between Islamic and nationalist groups in the history of the basic formulation of the Indonesian state became the source of this research data. Four indicators of religious moderation formulated by the Ministry of Religious Affairs of the Republic of Indonesia became analytical theories in this study, including national commitment, tolerance, anti-violence, and accommodating to local culture. Data collection through documentation. The results showed that there are various indicators of religious moderation by Islamic groups in the history of acceptance of the basic consesus of the Indonesian state. First, indicators of tolerance and anti-radicalism in respecting and accepting the abolition of the 7 Words in the Jakarta Charter. Second, the indictor of national commitment in maintaining the integration of the nation and state. Third, indicators of accommodative indicators of local wisdom in upholding a culture of deliberation related to the plurality of socio-political life. The theoretical implications of this study show that it takes a paradigm and religious attitude of individual (group) Muslims that is inclusive, tolerant, symbiotic in the life of a multicultural society. The limitations of the research have not examined the pattern of understanding or religious attitudes of Islamic groups that do not want the consesus of Pancasila and the 1945 Constitution in the history of the basic formulation of the Indonesian state. This is urgent to be studied further